Keterlibatan Anggota Dalam Struktur Organisasi Bascamp Pendakian Gunung, Untuk Mencapai Tujuan Bersama - Muhammad Khoerur Rizki; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The involvement of organizational members in the organizational structure of mountain basecamps is a key factor in achieving safety and success in expeditions. This study investigates the relationship between member involvement and safety and success in expeditions, and also measures the comfort of hiking participants by receiving complaints from hikers as evaluation material for organizational members to continuously develop facilities and other shortcomings complained about by participants. With high motivation from hiking participants towards the basecamp, it has a positive impact on its organizational structure. This evaluation framework was informed by extant organizational theories, including organizational structure, to establish a robust and standardized organizational system. It assesses the quality of services provided by the organization to external stakeholders, namely hiking participants, to gauge their level of satisfaction. Consequently, the engagement of external stakeholders is vital in fostering mutual comfort. The development of a standardized structure is crucial for organizational members.